Diplomatic documents data for international relations: the Freedom of Information Archive Database. (November 2021) - Connelly, Matthew J; Hicks, Raymond; Jervis, Robert; Spirling, Arthur; Suong, Clara H
We introduce the Freedom of Information Archive (FOIArchive) Database, a collection of over 3 million documents about state diplomacy. Substantively, our database focusses on the USA and provides opportunities to analyze previously classified (or publicly unavailable) corpora of internal government documents which include the raw—often full—text of those documents. We also provide within-country diplomatic records for the USA, UK, and Brazil. The full span of the data is 1620–2013, but it is mainly from the twentieth century. Our database allows scholars to view text and associated statistics online and to download and view customized datasets via an application programming interface. We provide extensive metadata about the documents, including the countries and persons they mention, and their topics and classification levels. The metadata includes information we extracted with domain-specific, customized natural language processing tools. To demonstrate the potential of this data, we use it to design and validate a new index for "country importance" in the context of US foreign policy priorities.